2019
DOI: 10.3280/efe2019-001004
|View full text |Cite
|
Sign up to set email alerts
|

Meta-review of Belgium's integrated National Energy and Climate draft Plan 2021-2030

Abstract: The EU energy & climate policy requests from all Member States to submit a National Energy & Climate Plan (NECP) over the year 2019, to reach the aggregate goals of energy efficiency, renewable energy supplies and greenhouse gas emissions reductions by 2030. The complicated Belgian context is briefly described. Then the many comments on Belgium's draft NECP are summarized and annotated. Commentators are the European Commission, various statutory advisory councils on energy and climate policies, NGOs, consultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 3 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…Considering country-specific analyses, the following few papers provide specific insights. Laes and Verbruggen (2019) analyzed the Belgian case, raising doubts about Belgium's ability to meet its commitments in a complex context. Cruciani and Geoffron (2019) analyzed the French case and reported that significant uncertainties remain while the targets are ambitious.…”
Section: Introductionmentioning
confidence: 99%
“…Considering country-specific analyses, the following few papers provide specific insights. Laes and Verbruggen (2019) analyzed the Belgian case, raising doubts about Belgium's ability to meet its commitments in a complex context. Cruciani and Geoffron (2019) analyzed the French case and reported that significant uncertainties remain while the targets are ambitious.…”
Section: Introductionmentioning
confidence: 99%